ANALISIS PROSPEK USAHA PENGOLAHAN IKAN ASIN DI KABUPATEN MIMIKA - Yassir Arafah; Yahya Nusa (CV. ADIBA AISHA AMIRA, 2023)
This research aims to find out how big the prospects for salted fish processing businesses are in Mimika Regency using aspects of SWOT analysis and Return Cost Ratio analysis, using descriptive methods which aim to find out strategies and determine the level of profit obtained by salted fish processing entrepreneurs. Data collection techniques are observation, questionnaires, interviews, and documentation. The analytical tools used are SWOT analysis to determine business prospect strategies and Return Cost Ratio analysis to determine the profits from production in the salted fish processing business in Mimika Regency. Based on the research results, the prospects for the salted fish processing business are in the supporting strategy quadrant, namely mobilizing all forces to take advantage of all existing opportunities. Meanwhile, cost efficiency has more than one value, which means that the salted fish processing business in Mimika Regency is efficient or profitable to run